Multi-Approach Investigation Regarding the West Nile Virus Situation in Hungary, 2018 - Zana, Brigitta; Erdélyi, Károly; Nagy, Anna; Mezei, Eszter; Nagy, Orsolya; Takács, Mária; Bakonyi, Tamás; Forgách, Petra; Korbacska-Kutasi, Orsolya; Fehér, Orsolya; Malik, Péter; Ursu, Krisztina; et al. (Viruses, 2020)
The West Nile virus is endemic in multiple European countries and responsible for several epidemics throughout the European region. Its evolution into local or even widespread epidemics is driven by multiple factors from genetic diversification of the virus to environmental conditions. The year of 2018 was characterized by an extraordinary increase in human and animal cases in the Central-Eastern European region, including Hungary. In a collaborative effort, we summarized and analyzed the genetic and serologic data of WNV infections from multiple Hungarian public health institutions, universities, and private organizations. We compared human and veterinary serologic data, along with NS5 and NS3 gene sequence data through 2018. Wild birds were excellent indicator species for WNV circulation in each year. Our efforts resulted in documenting the presence of multiple phylogenetic subclades with Balkans and Western-European progenitor sequences of WNV circulating among human and animal populations in Hungary prior to and during the 2018 epidemic. Supported by our sequence and phylogenetic data, the epidemic of 2018 was not caused by recently introduced WNV strains. Unfortunately, Hungary has no country-wide integrated surveillance system which would enable the analysis of related conditions and provide a comprehensive epidemiological picture. The One Health approach, involving multiple institutions and experts, should be implemented in order to fully understand ecological background factors driving the evolution of future epidemics.